Congenital Hydrocephalic Monster in an Indigenous Gir Calf: A Case Report - Borakhatariya, Devasee N; Raval, Rupesh J; Vala, Karsan B; Chavda, Bakti P; Prajapati, Sanny G (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
There are several types of fetal dropsy (fetal ascites, fetal anasarca, fetal hydrocephalus), which have obstetrical importance preventing normal easy delivery of calf. Hydrocephalus is one of the fetal causes of dystocia. It is characterized by an accumulation of fluid which may be in the ventricular system or between the brain and the subarachnoid space. The swelling or enlargement of cranium occurs as a result of an imbalance between formation and drainage of cerebrospinal fluid (Arthur et al., 2001). This congenital dropsical condition is associated with an autosomal recessive gene, whereas some cases are due to BVD-MD or bluetongue virus infection in bovine (Roberts, 1986). Though this dropsical condition is rare in Gir cattle, it is reported in many other species (Dhami et al., 2007; Kumar et al., 2010; Parmar et al., 2018). The present case report depicts an unusual instance of hydrocephalic monster in an indigenous Gir calf, causing dystocia, which was successfully managed by per vaginum.